Virtual Experiential Marketing Dan Sustainability-Oriented Innovation: (Studi Literatur Sistematis) - Luturmas, Fabiola Bulimasena; Maulita, Maulita; Syam, Herdi (Politeknik Negeri Ambon, 2024)
Virtual Experiential Marketing is a marketing strategy that enhances consumer experience by providing sustainable elements, such as interactive and memorable virtual experiences. This can increase consumer satisfaction and motivate them to participate in sustainable activities. The importance of Virtual Experiential Marketing in Sustainability-Oriented Innovation can be seen in things such as Virtual Experiential Marketing, which can increase customer satisfaction by providing a more personalized and interactive experience.The method used in this research is a systematic literature review with bibliographic analysis, used to identify research with the theme of Virtual Experiential Marketing and Sustainability-Oriented, using VOSViewer 1.6.19 software. Based on the clusters identified through the bibliography consisting of 494 selected articles, there are 11 clusters with 61 items related to Virtual Experiential Marketing and Sustainability-Oriented Innovation that can be suggested for future innovative research topics.